Asia's Changing Role in World Trade: Prospects for South - South Trade Growth to 2030 - Kym Anderson; Anna Strutt (Asian Development Bank (ADB), 2011)
Developing Asia's rapid economic growth has been shifting the global economic and industrial centers of gravity away from the North Atlantic, raising the importance of Asia in world trade, and boosting South–South trade. How will trade patterns change over the next 2 decades in the course of economic growth and structural changes in developing Asia and the rest of the world? In particular, what can be expected of developing Asia's intraregional trade and its trade with other developing country regions? This paper addresses these questions by projecting a core baseline for the world economy from 2004 to 2030 and comparing it with alternative scenarios for 2030. We employ the global economywide GTAP model and Version 7.1 of the GTAP database, and assume for the core projection that trade-related policies do not change over the next 2 decades. Alternative scenarios explore (i) slower economic growth rates in the "North", (ii) slower productivity growth in primary sectors, and (iii) various trade policy reforms in developing Asia without and with policy reforms also in the "North" and in South–South trade. Projected impacts on international prices, sectoral shares of regional gross domestic product and trade, "openness" to trade, and welfare gains from trade reforms are highlighted, in addition to their effects on regional shares of global gross domestic product and trade. The paper concludes by drawing out implications for regional and multilateral trade policy.
hdl:11540/2019
Keywords: D58; F17; Q17; Q24; Q54; 330; Global computable general equilibrium model projections; crop and labor productivity growth; Wirtschaftswachstum; Strukturwandel; Asien; Internationale Wirtschaftsbeziehungen; Handelsliberalisierung; Außenhandelsstruktur; Süd-Süd-Beziehungen; Welt